c.5 - Pieris Ralph (New Delhi, 1977)
The diversity of Asian social, political and economic systems has hampered comparative analysis of development in a vast region. In this book, originally planned as an essay on social development in Asia, the author has applied the unified approach to development analysis and planning evolved by the United Nations in general terms, to the Asian situation. It abandons the differentiation of social, political and economic sectors as inappropriate, and instead differentiates various styles of development in Asia, ranging from the post-industrial to the socialist style. Seven general criteria which determine a given style of development include autonomy and self sufficiency, popular participation, distribution of the fruits of development, protection of the environment and of human relationships contributing to solidarity, security, self-realization and freedom, are analyzed in the Asian context. At a time when Asian countries are sceptical of the feasibility and desirability of blind imitation of western models, the undesirable consequences found in some "follower societies" of Asia, particularly the parasitic involution of capitalism are considered. The concluding chapters deal with the delivery of social services and patterns of social welfare. In general this study utilizes the tool of styles of development to assess progress in terms of indigenous ideals, goals and values, rather than the yardsticks for measuring development evolved by and for the west.
Keywords: Social change -Economic development